Slang Words Found In Nicky Minaj's Songs - Sabila, Cindy; Irawan, Andi Muhammad (English Language and Literature, 2023)
This research aims to identify types of slang words and calculate the types of slang words that often appear in Nicky Minaj's song lyrics. This study used Allan and Burridge's (2006) theory of slang words to analyze the data. This research obtained data from transcripts obtained from the internet. The researcher searched for and collected the three required song lyrics which contained the data the researcher needed. The researcher read the song lyrics intensively, that is, the researcher analyzed the research and focused on the data. Based on the analysis found, researchers found 40 slang words in Nicky Minaj's song lyrics. Researchers found 20 slang words with the clipping type (50%), ten slang words with the fresh and creative type (25%), one slang word with the flippant type (2.5%), three slang words with the imitative type (7.5 %), and six slang words with acronym type (15%). The most dominant type of slang word in Nicky Minaj's song lyrics is clipping.